Perencanaan Pembangunan Kelurahan di Kelurahan Semanggi Kota Surakarta - Purwandari, Any Wahyu; Mussadun, Mussadun (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
The key to the implementation of the Village Development Planning Forum (Musrenbangkel) is community participation, so that the priority of development programs in accordance with community needs. However, there is a decrease in the implementation of community participation because no realization of development programs proposed society, especially the poor, as well as the implementation tends to be formal and monotonous so as to make people bored and tired. It happened also in the Kelurahan Semanggi which has the densest population with the highest number of poor people in Sub District of Pasar Kliwon. Under these conditions, the purpose of this study was to determine the public participation in the implementation of Musrenbangkel in Kelurahan Semanggu by reviewing Musrenbangkel process, forms of public participation, the level of community participation, as well as internal and external factors that affect the level of community participation. The method used is descriptive quantitative with a Likert scale for questionnaire, frequency distribution and multiple linear regression, as well as qualitative descriptive with purposive sampling and snowball sampling. This study shows that the bottom-up approach to the implementation of Musrenbangkel only be a compromise because the people (still) very dependent on the role of community and government leaders, as well as very poor community initiatives that the government (still) in control in determining development priorities.